Evaluasi Biaya Pengembangan Sistem Reservasi Online Gedung Serbaguna PT GHL Peninsula Menggunakan Metode Advance Use Case Point dan Revised Use Case Point (Studi Kasus: CV Gumcode Indonesia) - Savira Fahrunisa; Mochamad Chandra Saputra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In the software development industry, calculating software development cost estimation was an important activity. Many software development projects have failed due to inaccessibility limits, cost and time. CV Gumcode Indonesia was experience in similar problems, where there were many projects delayed and cost overrun so that an evaluation of how they estimated the cost was performed. This study described the cost, time and resource estimation needed for development by referring to Work Breakdown Structure and scheduled it into Gantt Chart using Advance Use Case Point and Revised Use Case Point methods. Data collection was done by interview technique to Project Manager and observation on the software, which processed into use case diagram and use case scenario. Advance Use Case Point method produced an estimation of hours of effort for 2.229,4 working hours with total cost Rp 110,558,733.00 and worked by 26 people. Revised Use Case Point method produced an estimation of hours of effort for 1.679.8 hours working with total cost Rp 83.303.382,00 and worked by 26 people. Based on the results of comparison analysis, Advance Use Case Point method was recommended because it covered the End-User Development features required in the Sistem Reservasi Online Gedung Serbaguna PT GHL Peninsula.